Discovering the Relationships Between Uncertainty Utterances and Knowledge Building in Cross-culture Online Collaborative Learning (International Conference on Computers in Education, 2020)
Previous studies focus on uncertainty expressions and how it is managed among basic and secondary education level students in a collaborative learning context. Although it has been reported that uncertainty serves as a motivation for learning, little is known about how it relates to knowledge building. In this paper is presented an essential aspect of the research area which focuses on uncertainty utterances and how they relate to knowledge building. This study seeks to examine how graduate students communicate, negotiate their uncertainties during online collaborative discussion writing to build on their knowledge and determine the relationship between uncertainty utterance and knowledge building. Insights into the data collection and proposed method of analysis are discussed. and explanation from peers. The findings of this study will pave the way for future studies to investigate uncertainty in different geographical contexts and subjects or courses.